STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI MIS ATTAQWA 51 - Mashuriyah Mashuriyah; Muhamad Taufik Bintang Kejora (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2022)
Educational leadership holds is valuable in guiding and mobilising educational companies to achieve the expected goals (Saunders, 1965:39). Educational leadership is a process of influencing, coordinating, mobilising, and changing society’s behaviour to get a proper education. The research objective is to identify the strategies and obstacles that will be faced by the headmaster in increaasing the teacher’s performance of MIS ATTAQWA 51 Bekasi. The method used in this research is a descriptive and qualitative approach. The information collecyed by consultation and observation. The results of this reserach: 1)the school leader’s strategy in increasing the capacity of the teachers : giving assignnments according to graduates, giving a chance to attend a training. 2) the school leader’s strategy in increasing the discipline of the teachers: enforcing the rules that existed in school, introducing a punishment. 3) the school leader’s strategy in advancing the passion of the teachers: creating a balanced position, grouping the teachers equal to their qualifications, equipping the teacher’s equipmeent to help them complete their tasks and giving reward and punishment. 4) the obstacles in creasing the performance of the teachers are inadequate school facilities.